Implementación de una página web y aplicación celular, para el monitoreo y registro para el parqueo de la Universidad Técnica de Cotopaxi extensión La Matriz. - Amores Travez, Washington Daniel (2024)
Globally, the development of technology has played a crucial role in the transformation of parking systems. From deploying smart sensors to creating mobile apps and dedicated websites, cities are constantly looking for improved solutions to effectively manage the supply and demand of parking spaces. Immersed in the beauty of the central Sierra of Ecuador, the city of Latacunga has experienced significant demographic and urban growth in recent years. This prosperity, although positive in many ways, presented significant challenges for the management of vehicle parking, making it a key factor for urban mobility and sustainability. In this sense, the implementation of a website and a mobile application for the control and registration of parking in the Matriz extension of the Technical University of Cotopaxi is documented and examined and highlights how this initiative reflects global trends in the search for technological solutions. to the current parking problem. Use Bootstrap's grid system to achieve responsive and consistent design across platforms, JavaScript is essential for modern web development as it enables the creation of interactive and dynamic experiences for users, Responsive design Bootstrap is designed to be Fully responsive, meaning apps and websites built with Bootstrap will automatically adapt to different screen sizes, from mobile devices to desktop screens.